2014
DOI: 10.1021/cm501596s
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Low-Cost Paper-Based Microfluidic Devices by Embossing or Cut-and-Stack Methods

Abstract: More detailed details on the dimensions of the dies, additional devices and videos of the running experiments are available in the supporting information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
113
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(115 citation statements)
references
References 34 publications
2
113
0
Order By: Relevance
“…When such pressure is targeted/localized, and with the appropriate lubrication to mitigate fiber damage, a channel can be created (Figure 2(a)). We 28,29 and others 5,[30][31][32][33][34][35][36] have shown that paper can be rendered hydrophobic by treatment with alkyl trichlorosilanes (Figures 1(b) and 1(c); see details in the supplementary material Figure S1). 29 We, therefore, hypothesized that co-deposition of an appropriately functionalized silane during the asymmetric calendaring could lead to a channel with desired wetting properties.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…When such pressure is targeted/localized, and with the appropriate lubrication to mitigate fiber damage, a channel can be created (Figure 2(a)). We 28,29 and others 5,[30][31][32][33][34][35][36] have shown that paper can be rendered hydrophobic by treatment with alkyl trichlorosilanes (Figures 1(b) and 1(c); see details in the supplementary material Figure S1). 29 We, therefore, hypothesized that co-deposition of an appropriately functionalized silane during the asymmetric calendaring could lead to a channel with desired wetting properties.…”
Section: Introductionmentioning
confidence: 92%
“…To validate the capability of fabricated channels as microfluidic devices, a "Y" design was used for fluid flow and theoretically compared with the literature (Figures 3(a)-3(c)). 5,8,10,11,14,16,18,20,[37][38][39][40][41][42][43] Other geometries were also fabricated (Figures 3(d) and 3(e)) to show the versatility of the targeted asymmetric calendaring and hydrophobization (TACH) method. The microfluidic devices were manufactured using paper and tested with dyed water (food color) for visualization.…”
Section: B Channel Fabricationmentioning
confidence: 99%
See 3 more Smart Citations